The decolorization of paint wastewater by using titanium dioxide and UV radiation (Photocatalysis) / Maizatul Ekmalia Jasni - Jasni, Maizatul Ekmalia (Faculty of Applied Sciences, 2009)
This study is to investigate the feasibility of using a combination of chemical coagulation and photocatalysis for decolourization and COD reduction of emulsion paint wastewater. The optimum pH, dosages of coagulant and flocculant in the jar test are 6.5, 0.024% of alum and 0.024% of CaC03.The resulting supernatant was subsequently treated with T1O2 and UV radiation for a fixed duration of 24 hours. It was observed that the average reductions of color and COD achieved are 93.4% and 97.1 % respectively for both samples. However, the quality of the final effluent still exceed the discharge limits of Department of Environment (DOE).Thus, further studies should be conducted in photocatalysis to improve the quality of the treated effluent.